Viral induction and targeted inhibition of galectin-1 in EBV + posttransplant lymphoproliferative disorders - Ouyang, Ying (2011)
Posttransplant lymphoproliferative disorders (PTLDs) are potentially fatal, EBVdriven B-cell malignancies that develop in immunocompromised solid organ or hematopoietic stem cell recipients. In PTLD, the expression of EBV proteins, including latent membrane protein 1 (LMP1) and LMP2A, viral immune evasion strategies, and impaired host immune surveillance foster the proliferation of EBV-transformed B cells. Current PTLD treatment strategies include reduction of immunosuppression, which increases the risk of graft rejection, anti-CD20 treatment, combination chemotherapy, and administration of EBV-specific cytotoxic T cells. In the present study, we report that EBV-transformed lymphoblastoid Bcell lines (LCLs) and primary PTLDs overexpress galectin-1 (Gal1), a carbohydratebinding lectin that induces tolerogenic dendritic cells and triggers the selective apoptosis of CD4 Th1 and Th17 cells and cytotoxic T cells. In transcriptional reporter assays, LMP2A and LMP1 each increased Gal1-driven luciferase expression, and the combination of LMP2A and LMP1 was additive. In addition, small interfering RNA (siRNA)–mediated depletion of LMP2A decreased Gal1 protein abundance in EBV-transformed LCLs. Gal1 expression in LCLs was dependent on both activating protein 1 (AP-1) and PI3K. A newly developed neutralizing Gal1 mAb selectively inhibited Gal1-mediated apoptosis of EBV-specific CD8 T cells. Given the tolerogenic and immunosuppressive function of Gal1, antibody-mediated Gal1 neutralization may represent a novel immunotherapeutic strategy for PTLD and other Gal1-expressing tumors.